2009
DOI: 10.1007/s11127-009-9563-3
|View full text |Cite
|
Sign up to set email alerts
|

Public servants in parliament: theory and evidence on its determinants in Germany

Abstract: Political selection, Parliamentary election, Public servants, Incompatibility, D72, D73, H11, H83,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…To allow a consistent estimation, we instrument the fraction of public servants with the respective institutional determinants that are not themselves explanatory variables for parliamentary oversight. These instruments are taken form Braendle and Stutzer (2010). Braendle and Stutzer (2010) analyze the selection effects of institutional restrictions and privileges that apply only to public servants elected to parliament.…”
Section: Instrumental Variable Estimationsmentioning
confidence: 99%
See 3 more Smart Citations
“…To allow a consistent estimation, we instrument the fraction of public servants with the respective institutional determinants that are not themselves explanatory variables for parliamentary oversight. These instruments are taken form Braendle and Stutzer (2010). Braendle and Stutzer (2010) analyze the selection effects of institutional restrictions and privileges that apply only to public servants elected to parliament.…”
Section: Instrumental Variable Estimationsmentioning
confidence: 99%
“…These instruments are taken form Braendle and Stutzer (2010). Braendle and Stutzer (2010) analyze the selection effects of institutional restrictions and privileges that apply only to public servants elected to parliament. Examples are the varying degrees in the strictness of incompatibility rules or privileges, such as special pension benefits, automatic promotion and the abeyance compensation for being put on leave.…”
Section: Instrumental Variable Estimationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier study closely linked to the current analysis, Braendle and Stutzer (2010a) investigate the representation of public servants in German state parliaments. Using time-series crosssectional analysis, they found that institutional restrictions in terms of incompatibility rules substantially reduce the selection of public servants into parliament and that institutionally granted privileges increase the fraction of public servants.…”
Section: Introductionmentioning
confidence: 99%